Using Appreciative Inquiry to Explore the Potential of Enhanced Practice Education Opportunities. (September 2014) - Clarke, Maria; Thornton, Jacqui
This practice analysis demonstrates how appreciative inquiry has been used within a Local Health Board to enhance the quality of practice placements and increase the range of occupational therapy practice opportunities offered to students. A positively focused appreciative inquiry workshop, collaboratively facilitated between the Local Health Board and a university, brought about change. Both student placements and the range of placement opportunities increased, and occupational therapists and students reported greater confidence and improved experiences. The use of appreciative inquiry in discussion provided a guiding structure and a framework that enhanced and sustained positive change.